Students’ engagement in the medical school in Nepal based on ASPIRE criteria - Piryani, Rano Mal; Piryani, Suneet; Narayan, Gautam (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Students’ engagement in active learning and scholarly activities are essential for effective medical education. This is one of the dimensions of ASPIRE-to-Excellence-Initiative. Objective of this study was to know from students about their engagement in Universal College of Medical Sciences (UCMS) Bhairahawa, Nepal as per ASPIRE criteria for excellence. Material and methods: This is questionnaire-based survey done in UCMS, in October 2019. The Criteria regarding students’ engagement developed by International Association for Medical Education (AMEE)for ASPIRE-to-Excellence-Initiative was utilized in the questionnaire. The questionnaire comprised of four ASPIRE criteria and 21 sub-criteria. The response on each sub-criteria (statements) were three yes/to some- extent/no. They had to select one response as deemed appropriate. 3rd-year MBBS students participated in the survey. The data was entered into SPSS 21; frequency, and percentage were computed. Results: Out of 100 students; 80 participated in the survey. The response rate was 80%. Around 2/3 of the students reported that they didn’t engaged with management of the school, including matters of policy and mission and vision of the school. Overall students’ engagement is poor on criteria-1. More than 2/3 of the students mentioned that they have been engaged in the school’s education program (delivery of teaching and assessment). Overall students’ engagement is fair on criteria-2. More than 50% of students reported that they have been engaged in the academic community (school’s research program and participation in meetings). Overall students’ engagement is satisfactory on criteria-3. More than 70% of students mentioned that they have been engaged in the local community and service delivery. Overall students’ engagement is good oncriteria-4. Conclusion: Students’ engaged on 4 criteria varies from poor to good; poor on criteria 1 while good on criteria 4. More research is required involving all batches of students and other medical colleges in Nepal to know the details of students’ engagement in medical schools based on ASPIRE criteria.